Estrogeni hormoni in estrogensko delujoči kemijski motilci endokrinega sistema - Grobin, Andrej (Farmacevtski vestnik, 2022)
Estrogen hormones and estrogenically active endocrine disruptors are substances, which we come into daily contact with in the environment through food and water. Apart from their classic mechanisms of action which are receptor mediated, they also elicit effects on the expression of genes in the human body. Currently, the most researched mechanisms affecting gene expression are DNA methylation, histone modification and effects via long non-coding RNA and microRNA. Some of these effects have already been determined in in vitro, as well as in in vivo tests, in the case of BPA even in environmentally relevant concentrations. Lately, we are being subjected to new types of previously unknown endocrine disruptors. The issues stem from the fact that we currently have limited analytics available for detecting all these substances in the environment and humans with tests, which are not systematic enough in determining the toxicity of the aforementioned substances caused by synergistic effects they have on DNA expression.
Keywords: bisfenol A (BPA); Endokrinologija; Epigenetika; Estrogeni; estrogeni hormoni; Hormonski motilci; izražanje DNA; kemijski motilci endokrinega sistema